Dirty beasts - Dahl, Roald; Blake, Quentin (London Puffin Books, 2016)
A collection of humorous poems about amazing or nasty creatures, including a flying cow, a pig who turns the tables on a farmer, and crocodiles, lions, and anteaters who delight in devouring people.
Keywords: Animals -- Juvenile poetry; Children's poetry, English; Animals -- Poetry; Humorous poetry; English poetry